Fault activity in the epicentral area of the 1580 Dover Strait (Pas-de-Calais) earthquake (northwestern Europe) - Garcia-Moreno,D; Verbeeck,K; Camelbeeck,T; De,Batist M; Oggioni,F; Hurtado,OZ; Versteeg,W; Jomard,H; Collier,JS; Gupta,S; Trentesaux,A; Vanneste,K (Geophysical Journal International, 2015)
On 1580 April 6 one of the most destructive earthquakes of northwestern Europe took placein the Dover Strait (Pas de Calais). The epicentre of this seismic event, the magnitude ofwhich is estimated to have been about 6.0, has been located in the offshore continuationof the North Artois shear zone, a major Variscan tectonic structure that traverses the DoverStrait. The location of this and two other moderate magnitude historical earthquakes in theDover Strait suggests that the North Artois shear zone or some of its fault segments may bepresently active. In order to investigate the possible fault activity in the epicentral area ofthe AD 1580 earthquake, we have gathered a large set of bathymetric and seismic-reflectiondata covering the almost-entire width of the Dover Strait. These data have revealed a broadstructural zone comprising several subparallel WNW–ESE trending faults and folds, some ofthem significantly offsetting the Cretaceous bedrock. The geophysical investigation has alsoshown some indication of possible Quaternary fault activity. However, this activity only appearsto have affected the lowermost layers of the sediment infilling Middle Pleistocene palaeobasins.This indicates that, if these faults have been active since Middle Pleistocene, their slip ratesmust have been very low. Hence, the AD 1580 earthquake appears to be a very infrequentevent in the Dover Strait, representing a good example of the moderate magnitude earthquakesthat sometimes occur in plate interiors on faults with unknown historical seismicity.